Urgensi Pendidikan Karakter dalam Membentuk Akhlak Peserta Didik - Rony Rony; Siti Ainun Jariyah (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2020)
Character education in Indonesia needs to be instilled from an early age, given the decline in morality of students in the era of globalization. Morality is an element that shows the quality of people's lives. Religious people assume that religion always teaches its followers to do good and prohibits them from doing wrong. Meanwhile, humanists assume that a person's morality is seen from how someone obeys the values ​​and norms in society. Cultivating character education through three stages, namely internalization and externalization. The three processes of planting can show positive results, of course, the character of the students is also good. However, if the three processes are not optimal, the results obtained by students are also not optimal. The internalization process becomes the basic process or foundation for the character education of students, where the family forms the basis of a character in the form of character recognition to students. And externalization is the next process of internalization where this process is filled by education staff, peers, social media.